2019
DOI: 10.1002/jper.18-0729
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel salivary biomarker miR‐143‐3p for periodontal diagnosis: A proof of concept study

Abstract: Background Though the use of salivary miRNAs as potential biomarkers has been reported in few diseases/conditions such as rheumatoid arthritis and oral cancer, there are no reported studies on their utility in periodontal diagnostics. Thus, the aim of the present study was to profile salivary miRNAs and identify the most suitable salivary miRNA biomarker in chronic periodontitis. Methods In this study, we have explored the potential application of next generation sequencing (NGS) technology for profiling miRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 49 publications
1
27
0
Order By: Relevance
“…Although most research identified different expression levels of miRNAs in periodontal and peri-implant diseases compared to their counterparts, their actual role in the pathogenesis of these conditions remains unclear. Conversely, miRNAs have been proposed as valuable future diagnostics tools in periodontal and peri-implant diseases as high-quality miRNAs are reportedly detectable in oral fluids [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Although most research identified different expression levels of miRNAs in periodontal and peri-implant diseases compared to their counterparts, their actual role in the pathogenesis of these conditions remains unclear. Conversely, miRNAs have been proposed as valuable future diagnostics tools in periodontal and peri-implant diseases as high-quality miRNAs are reportedly detectable in oral fluids [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…High-throughput data were widely used in various elds including periodontitis. Yuko et al used methylation array to identify periodontal disease-related methylation sites [12], K et al used miRNA array detecting miR143-3p as a novel salivary biomarker for chronic periodontitis [13], and M et al used gene array identifying distinct periodontitis subtypes [14]. However, in these studies high-throughput data were not fully used, only routine analysis has been performed and only a little useful information was generated from the numerous results.…”
Section: Introductionmentioning
confidence: 99%
“…These polymorphisms are variations in the genetic code that can have different effects, for example, changing the levels of gene expression, causing slight functional changes of the coded molecules, making individuals more susceptible to the onset of a certain disease or to the appearance of clinical pictures more serious than the disease itself [9].…”
mentioning
confidence: 99%